The rise of the novel - Seager, Nicholas (Readers' guides to essential criticism, 2012)
This guide explores the dominant methodologies, theories and debates surrounding the emergence of the novel during the 18th-century. Covering key criticism on authors such as Defoe, Fielding, Richardson and Austen, the emphasis is on how critical work is interrelated, allowing readers to discern trends in the critical conversation.